Strategic patterns in the development of network capability in new ventures - O'Toole, Thomas; McGrath, Helen (Industrial marketing management, 2018)
This paper seeks to examine the strategic patterns in the development of network capability in new ventures. Every firm needs to build on their internal resources to survive and grow. In this respect, network capability development is important for new ventures to acquire and mobilize external resources and engage in interactive networked activities. Strategizing and new venture contexts are relatively new streams of research for the Industrial Marketing & Purchasing (IMP) group. Based on a longitudinal case study of two new ventures, our findings add to this largely emerging field suggesting that there are two viable pathways for strategizing for network capability development, emergent and deliberate. Further, the cases demonstrate nine patterns evident in the two strategy-making processes. Our paper adds to the growing body of literature that places interaction, relationships, and networks at the heart of strategy making and provides important insights for new ventures, which may lead to earlier and greater success for the firms.